Effects of strain on boundary management: findings from a daily diary study and an experimental vignette study - Mueller, Nicolas; Loeffelsend, Sophia; Vater, Elke; Kempen, Regina (Frontiers in Psychology, 2023)
Introduction Transformations in the work–nonwork interface highlight the importance of effectively managing the boundaries between life domains. However, do the ways individuals manage the boundaries between work and nonwork life change from one day to the next? If so, which antecedents may explain these intra-individual fluctuations in boundary management? Drawing on boundary management, spillover, and resource theories, we investigate daily changes in segmentation preferences and integration enactments as a function of experiencing strain in work and nonwork life. Assuming that changes in segmentation preferences reflect an individual’s strategy to regulate negative cross-role spillover, we suppose that strain increases individuals’ segmentation preferences; at the same time, however, it could force individuals to enact more integration. Methods We test our assumptions with data from two studies with different methodological approaches. The first study uses a daily diary research design (Study 1, 425 participants with 3,238 daily observations) in which full-time professionals rated strain in work and nonwork life, segmentation preferences, and integration enactments every evening for 10 workdays. The second study uses an experimental vignette research design (Study 2, 181 participants), where we experimentally manipulated strain in work and nonwork life and investigated causal effects on participants’ hypothetical segmentation preferences. Results The results of multilevel modeling analyses in Study 1 show that segmentation preferences and integration enactments fluctuate from day to day as a function of strain. More specifically, strain is related to preferring more segmentation but enacting more integration. Study 2 replicates the results of Study 1, showing that strain causally affects segmentation preferences. Discussion This two-study paper is one of the first to address daily fluctuations in segmentation preferences and integration enactments, extending our knowledge of temporal dynamics in boundary management. Furthermore, it demonstrates that strain is an antecedent of these daily fluctuations, offering starting points for practical interventions.